Ultraestructure and cytochemistry of colleters in Apocynaceae - Ribeiro, Josiana Cristina (2017)
The colleters of Apocynaceae are glands related to different types of protection of vegetative and floral meristems through the production of mucilage or a mixture of many different compounds. Although several anatomical papers have shown histological and histochemical aspects of colleters of the family, almost nothing is known about the secretory process of the cells of this gland. In this paper we studied two types of colleters that occur in the family: what produces exclusively mucilaginous secretion and what produces mucilage and lipophilic compounds, being analyzed in two species for each type of colleter. The secretory epidermis of the colleters of Allamanda schottii and Blepharodon bicuspidatum presents a large amount of dictiosomes and endoplasmic reticulum, a dispersed vacuoma composed of small vacuoles with fibrilar osmiophilic material, leucoplasts with large amount of starch and few thylakoids, as well as large mitochondria. The mode of secretion release is granulocrine and the exudate crosses the cuticle without breaking it by projections of pectin reaching the surface. The secretory cells of the colleters of Mandevilla splendens and Peplonia axillaris have completely different ultrastructure and secretion from those of Allamanda schottii and B. bicuspidatum. Plastids and mitochondria are observed, as well as a profusion of dictiosomes and their vesicles in association with the rough endoplasmic reticulum near the cell membrane. The secretion is mainly observed in the cisterns and vesicles of the trans face of the dictiosomes, indicating the production of a great amount of mucilage. The mechanism of secretion release is also granulocrine, but the secretion is temporarily accumulated in a large periplasmic space before crossing the cell wall and the cuticle. Two distinct patterns of secretion production and release were found in the colleters of Apocynaceae that are related to the composition of the secretion and not to the group to which the species analyzed belong. Although the colleters in the family are histologically similar, the present paper demonstrates a metabolic and subcellular variability until then unknown to the group